Pemikiran Cak Nur Terkait Perempuan dan Feminisme Dalam Perspektif Islam - Hidayatulloh, Taufik; Ayu Zumro’atus Sholihah (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Nurcholish Madjid, who is usually called Cak Nur, is an Indonesia Islamic thinker, scholar and cultural figure. Cak Nur often expresses various ideas and views on many things, especially the idea of islamic reform in Indonesia. Women and Feminism are oftem discussed from various perspectives, including the Islamic perspective. Women and Feminism are also not lost on Cak Nur, even though Cak Nur does not explain it specifically in the works he has written. This research is aimed at exploring Cak Nur’s thoughts regarding women and feminism specifically and from an Islamic perspective. This research uses a qualitative approach by analizing reliable sources from Cak Nur’s thoughts and work as well as from related research sources. As a result of this research, Cak Nur views that all humans are the same, both men and women, equally serve God and have the same rights and obligations. This understanding is the same as the Islamic perspective, that God never differentiates between His servants, even women and men are not differentiated in the Qur’an.